2012
DOI: 10.1163/156856111x600235
|View full text |Cite
|
Sign up to set email alerts
|

Wetting Transition on Micro/Nanostructured ZnO Layers

Abstract: This paper reports on the electrowetting behavior on three micro/nanostructured ZnO (zinc oxide) layers with different roughnesses. ZnO nanorods with diameters of 100 nm and heights of 1 µm (sample A), 3 µm (sample B), and micro flower-like layer with a diameter of 5 µm (sample C) were fabricated on the ITO glass substrates. This was followed by deposition of Teflon to achieve superhydrophobic property on the prepared surfaces. On these three Teflon modified ZnO layers, reversible electrowetting phenomenon was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Under the dc or ac electric field, the electroinduced surface wettability conversion from the superhydrophobic to hydrophilic state was observed and the generation of surface defective sites on ZnO films under electric field was used to explain the transition mechanism. Electroinduced surface wettability conversion is also studied by other researchers [70,71]. It is found that the reversibility of wettability conversion is dependent on the structure types.…”
Section: Electrochemical Methodmentioning
confidence: 96%
“…Under the dc or ac electric field, the electroinduced surface wettability conversion from the superhydrophobic to hydrophilic state was observed and the generation of surface defective sites on ZnO films under electric field was used to explain the transition mechanism. Electroinduced surface wettability conversion is also studied by other researchers [70,71]. It is found that the reversibility of wettability conversion is dependent on the structure types.…”
Section: Electrochemical Methodmentioning
confidence: 96%